Ekshumacijos aktų klastotės vertinant 1941 metų Utenos žydų sunaikinimą Rašės miške, ir ne tik. - Vitkus, Aleksandras (Genocidas ir rezistencija, 2020)
Rašės Park is located in Utena, in a north-eastern area of the town. The territory of the park covers the part of the valley of the Rašė River from Užpalių Street to the Kloviniai (Utena) pond. The park features a monument commemorating the Jews who were murdered by the Nazis in 1941 in Utena County. The inscription on the monument in Yiddish and Lithuanian reads: “In this place, Hitler’s executioners and their local accomplices murdered about 8,000 Jews: men, women and children in July–August 1941.” The aim of our work is to give as realistic a figure as possible for the number of Jews killed, so we first present a table in which, according to the data from press publications and Lithuanian Special Archives files, witnesses give their versions of the number of Jews killed.
Keywords: German occupation; jews; Holocaust; Utena